A Bio-Medical Informatics Perspective on Human Factors - Ruch, P.; Managing Editor for the IMIA Yearbook Section on Human Factors (Yearbook of Medical Informatics, 2008)
Objectives To summarize current excellent research in the field of human factors.MethodsWe provide a synopsis of the articles selected for the IMIA Yearbook 2008, from which we attempt to derive a synthetic overview of the activity and new trends in the field.Results while the state of the research in the field of human factors is illustrated by a set of fairly heterogeneous studies, it is possible to identify trends. Thus, clearly, the importance of issues related to medical order entry, which also founded human factors studies in medical informatics, still occupies a central role in the field. In parallel, we observe an emerging interest for human factors from the field of bioinformatics, where the mass of data generated by high/ throughput experiments and large-scale genome analysis projects, raises specific processing challenges. Such challenges will have to be addressed to achieve post-genomics era medicine.Conclusions The best paper selection of articles on human factors shows examples of excellent research on methods concerning original development as well as quality assurance of previously reported studies. The crucial role of preserving interpersonal communication among healthcare staff in computerized working environments is complemented by more original scientific investigations, which demonstrate the needs for computerized applications to transform the biomedical data overflow into more operational clinical knowledge. Altogether these papers support the idea that more elaborated computer tools, likely to combine contextual contents, are needed.
Keywords: Medical informatics; International Medical Informatics Association; yearbook; human factors